Identity & Promotional Media of Diradio.Net - Deri Deri; Bijaksana Prabawa (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2014)
Entering the digital era, a variety of conventional information media transformed into a medium that is based on digital technology. The development of digital information media is capable of providing tremendous influence on human behavior change. One among these is media streaming radio.Expediency owned by streaming radio, not merely make this medium easily accepted by the public.Diradio.net is one company that provides streaming radio services. Unfortunately the market acceptance of the products offered by diradio.net are not too high. The problem of lack of information and education about this new media lead to low use of streaming radio. Other internal problems arise in this company, which is a mismatch in the determination of the target market.Various data obtained through observation, library research, as well as interviews with some input on this design process. Data obtained was analyzed and showed that the company requires a new identity more in line with its target market. The results of further analysis is needed promotional media can educate the market about the benefits of streaming radio. As for the media that is designed magazine ads, e-posters, flyers, stickers, x-banners, t shirt, Sticker gadgets, ambient media, booths, billboards, car operations, web banners, and social media. Through a media campaign is expected that more people are using streaming radio, especially through service diradio.net